Recent advances in nanomaterial-driven strategies for diagnosis and therapy of vascular anomalies - Yiming Geng; Huwei Zou; Zhaowei Li; Haiwei Wu (Journal of Nanobiotechnology, 2024)
Abstract Nanotechnology has demonstrated immense potential in various fields, especially in biomedical field. Among these domains, the development of nanotechnology for diagnosing and treating vascular anomalies has garnered significant attention. Vascular anomalies refer to structural and functional anomalies within the vascular system, which can result in conditions such as vascular malformations and tumors. These anomalies can significantly impact the quality of life of patients and pose significant health concerns. Nanoscale contrast agents have been developed for targeted imaging of blood vessels, enabling more precise identification and characterization of vascular anomalies. These contrast agents can be designed to bind specifically to abnormal blood vessels, providing healthcare professionals with a clearer view of the affected areas. More importantly, nanotechnology also offers promising solutions for targeted therapeutic interventions. Nanoparticles can be engineered to deliver drugs directly to the site of vascular anomalies, maximizing therapeutic effects while minimizing side effects on healthy tissues. Meanwhile, by incorporating functional components into nanoparticles, such as photosensitizers, nanotechnology enables innovative treatment modalities such as photothermal therapy and photodynamic therapy. This review focuses on the applications and potential of nanotechnology in the imaging and therapy of vascular anomalies, as well as discusses the present challenges and future directions. Graphical Abstract